2021
DOI: 10.1089/heq.2020.0159
|View full text |Cite
|
Sign up to set email alerts
|

Patients' Perspectives on the Feasibility, Acceptability, and Impact of a Community Health Worker Program: A Qualitative Study

Abstract: Purpose: To examine patients' perceptions of the feasibility, acceptability, and impact of a safety net-based community health worker (CHW) program. Methods: Semistructured interviews with patient participants diagnosed with type 2 diabetes (n = 13) were analyzed using a traditional text analysis method based on grounded theory. Results: This study highlights that the CHW program can improve satisfaction in accessing health services and community resources, and overall health outcomes of patients in safety net… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(23 citation statements)
references
References 12 publications
1
22
0
Order By: Relevance
“…Related to this, CHWP training varied from a brief induction delivered by research staff ( 58 ) to an in-depth training programme with regular updates delivered by local health care providers ( 61 ). In studies the training regime was often poorly described or inconsistent making it difficult to evaluate the resulting impact on intervention quality ( 49 , 52 , 55 , 56 , 60 , 63 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Related to this, CHWP training varied from a brief induction delivered by research staff ( 58 ) to an in-depth training programme with regular updates delivered by local health care providers ( 61 ). In studies the training regime was often poorly described or inconsistent making it difficult to evaluate the resulting impact on intervention quality ( 49 , 52 , 55 , 56 , 60 , 63 ).…”
Section: Resultsmentioning
confidence: 99%
“…The physical and mental health of participants related to T2DM severity affected ability to attend sessions in two studies set in Latino populations ( 49 , 51 ). As one participant from a Latino population in Connecticut, USA explained:…”
Section: Resultsmentioning
confidence: 99%
“…As described by Boyd et al , this trust-based relationship was perceived by patients as being influential to the improvement in emotional well-being and health behaviours 24. Chang et al reported that in a CHW intervention focused on HbA1c outcomes, patients acknowledged how CHWs increased their skills and confidence to modify behaviours and achieve their goals 25. Another CHW quality that contributes to the SyV intervention is their ability to communicate complex information in a low-literacy manner, enhancing their communication with participants 26 27.…”
Section: Discussionmentioning
confidence: 96%
“… 24 Chang et al reported that in a CHW intervention focused on HbA1c outcomes, patients acknowledged how CHWs increased their skills and confidence to modify behaviours and achieve their goals. 25 Another CHW quality that contributes to the SyV intervention is their ability to communicate complex information in a low-literacy manner, enhancing their communication with participants. 26 27 One example of a curriculum designed for lower health literacy populations is the DEEP curriculum.…”
Section: Discussionmentioning
confidence: 99%
“…As found in other studies, CHWs tend to be accepted by their neighbors as they are commonly selected by communities they live among [49,62], which further increases the likelihood of outcomes including acceptability, feasibility, and equity. Implementation of this program mainly requires leadership follow-up and use of small budget, which helps with feasibility of its rollout [63,64]. In addition, sustainability of EBIs such as pneumococcal conjugate vaccine and rotavirus vaccination was mainly dependent on funding availability from both partners and governments.…”
Section: Discussionmentioning
confidence: 99%